(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Mosttheories of FDI have emerged during the post-war period, when the forces ofglobalization began to grow. The growing importance of MNC and FDI during thefifties and sixties gave an impetus to researchers to find theories able toexplain the behavior of MNC’s and the existence of international production.The early theories could only explain a limited share of the total FDI flows.These theories were also inadequate because they failed to bring out the factthat FDI is not only a capital flow but also constitutes a package includingother components such as management and technology transfer.